Hybrid nano‐ and microgels doped with photoacoustic contrast agents for cancer theranostics. Issue 6 (13th July 2021) - Xiao, Yu; Gateau, Jérôme; Silva, Amanda K A; Shi, Xiangyang; Gazeau, Florence; Mangeney, Claire; Luo, Yun
Abstract: Photoacoustic imaging (PAI) is an emerging noninvasive and inexpensive bioimaging modality, which has stimulated a wide interest in recent years for cancer theranostics. Hybrid nano‐ and microgels have been designed as protective carriers to incorporate PAI contrast agents due to their biocompatibility and biodegradability, high loading capacity, versatile surface chemistry, and stimuli‐responsive properties. These key features offer unprecedented opportunities for the design of innovative multifunctional cancer theranostic agents. This review focuses on the recent development of photoacoustic active nano‐ and microgels for biomedical applications in cancer theranostics and cancer hallmark imaging. The various chemical natures of gels and PAI contrast agents and the elaboration methods of hybrid matrices are summarized and discussed. Their applications in multimodal cancer theranostics and cancer hallmark imaging are presented, highlighting their merits and potential in treatment and diagnosis. Abstract : In this review, we introduce the basic concepts for the design of hybrid microgels in the domain of photoacoustic imaging (PAI). The methods to synthesize hybrid assemblies are described and their applications in cancer‐related PAI and biomedicine are summarized focusing on two main orientations: (i) multimodal cancer theranostics including PAI or/and synergistic therapy; and (ii) cancer hallmark detection and microenvironment investigation using PAI.